2015
DOI: 10.1111/aas.12588
|View full text |Cite
|
Sign up to set email alerts
|

Preserved oxygenation in obese patients receiving protective ventilation during laparoscopic surgery: a randomized controlled study

Abstract: A CPAP of 10 cmH2 O during pre-oxygenation and induction, followed by PEEP after intubation, seemed to preserve oxygenation during anaesthesia. Post-operative oxygenation depended on the FIO2 used during emergence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…Lee et al evaluated the optimal PEEP for RARP and found that 7 cm H 2 O of PEEP is suitable for RARP [ 34 ]. In the case of obese patients undergoing general anaesthesia, 10 cm H 2 O of PEEP improved respiratory parameters and oxygenation [ 35 , 36 ]. The other method is to change the inspiration:expiration ratio, to 1:1, for example [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al evaluated the optimal PEEP for RARP and found that 7 cm H 2 O of PEEP is suitable for RARP [ 34 ]. In the case of obese patients undergoing general anaesthesia, 10 cm H 2 O of PEEP improved respiratory parameters and oxygenation [ 35 , 36 ]. The other method is to change the inspiration:expiration ratio, to 1:1, for example [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…). Preoxygenation is enhanced by augmenting functional residual capacity using non‐invasive ventilation, which increases the safe apnoea period by 50 per cent. Use of second‐generation supraglottic devices before laryngoscope‐guided intubation may extend the safe apnoea period by 50 per cent, compared with preoxygenation with CPAP.…”
Section: Resultsmentioning
confidence: 99%
“…However, these effects can be mitigated by limiting the high FIO 2 to 0.8 55 and by using an adequate level of PEEP. 56 Moreover, Akça et al 55 used CT scans to show that there was no difference in postoperative atelectasis between 0.8 and 0.3 FIO 2 in patients undergoing abdominal surgery. Furthermore, Hovaguimian et al 26 confirmed these results in their meta-analysis which included randomised controlled trials comparing high to low FIO 2 .…”
Section: Discussionmentioning
confidence: 99%